Edible Cell Model For Cell Biology Learning For The Elementary School Students - Amelia Sendang Husin; F.D. Erika Setyajati; Vincentia Krisnina Prasetyo; Bakti Wahyu Saputra; Monica Cahyaning Ratri; Agustina Setiawati (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2022)
Learning cell biology in science subject is a challenging for elementary students in Indonesia. Not only it is implicitly taught in the science subject, but it also needs an intangible imagination to understand the cell’s organelles and their function. Therefore, a recreating method to explain about the cells the cell’s organelles and their function. In our program, the 5th and 6th of elementary students were explained about cells, organelles and their function in the first week class. Thus, they also were taught to observe cells under light microscope. Moreover, we developed the cells model by creating it from the edible materials such as cake, candies, messes, and biscuits; followed by fun game. While the cognitive ability of the students was evaluated with pre-and post-test. Our method increased the level of understanding of the students to learn cell biology. However, the standard deviation of student cognitive ability was highly varied in both classes.